Albatross Flight: Dynamic Soaring - Haultcoeur, Alice; Ingouf, Benoit; Bel, Florent; Pradier, Yvan (TMAL02 Expert Conference, 2020)
This article presents the flight of an albatross, and more precisely the survey of the dynamic soaring. It is the flying technique used by the bird to save energy.